In Search of the Genes of Asthma on the Island of Tristan da Cunha. Issue 1 (3rd March 1995) - Zamel, Noe
Abstract : Asthma, like several common diseases such as diabetes and atherosclerosis, occurs in families and thus probably has a complex polygenic basis, in which environmental factors also play a role. In trying to elucidate the genetic mechanism, studies of communities characterized by a high level of interbreeding and a high prevalence of asthma should be helpful. One such community has been described in the medical literature, the island of Tristan da Cunha. The University of Toronto Genetics of Asthma Project decided to study this community. It sent a team to the island to construct a geneology, obtain a history of respiratory and allergy symptoms by questionnaire, perform allergy skin testing and methocholine challenge, and obtain blood for white cell genetic studies. The initial results of this study are presented here, together with a historical perspective on the people of Tristan da Cunha.